Dependence on authority and exercising leadership in Hungary - Kowalik, Tamas (My University, 2025)
Hungary has been known for giving birth to many talents, manifested by a string of Nobel Prize laureates and what some say is the highest ratio of useful inventions per capita in the world—including the biro pen, the Rubik cube, and very distantly, the computer. Most of these talents left Hungary before achieving fame. The country’s loss of innovative capacity has been partly attributed to the way authority has been exercised: the strong authority context. This study explored the relationship between authority, dependence on authority, and leadership within the specific Hungarian context. It aimed to address three scholarly challenges: (a) situating authority in leadership theory, (b) moving away from a leader-centric approach to focus on participants’ lived experiences at the micro-level, and (c) transcending the “Western bias” by examining authority, dependence on authority, and leadership in an East-Central European context (Dugan, 2017, p. 135). This doctoral research was guided by the following questions: 1. How do participants describe and make sense of authority, dependence on authority and leadership in the Hungarian context? 2. What factors do participants describe as having an impact on the dependence on authority in the Hungarian context? 3. From participants’ experiences, in what ways does authority and dependence on authority affect leadership? The qualitative research utilized multiple theories, frameworks, and concepts, such as adaptive leadership, toxic leadership, power theories, the cycle of socialization, and followership theories. It employed abductive analysis methodology and involved thirteen participants who shared their lived experiences regarding authority, dependence on authority, and leadership through two rounds of in-depth focus group interviews. The findings revealed a social chain of dependence within Hungary’s hierarchical social structure and highlighted multiple barriers to exercising leadership in Hungary. Based on the findings, a new model, the Hungarian vicious circle, was developed. This model explains how the exercise of authority combined with the social context perpetuates dependence on authority, ultimately leading to a corrupted concept of leadership. The implications highlight the importance of citizens collaborating within their micro-environment to foster an enabling environment for leadership. It is also essential to provide training on how to exercise authority responsibly. Additionally, at the systems level, the values and mechanisms introduced by globalization along with the presence of international corporations, can positively impact strong authority contexts. Participants recommended fostering a mindset change through leadership development and encouraged efforts to attract Hungarians living abroad to return and share their experiences. Future research could include comparative studies with other similar strong authority contexts and may employ quantitative or mixed methods approaches to facilitate broader generalizations.
Keywords: Dependence on authority; Leadership; Hungary; Authority